TOOLS FOR DEVELOPING STUDENT DESIGN SKILLS IN CONSTRUCTION DIRECTIONS - Azamjon Komolkhanovich, Abdullaev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents methods and tools for developing students’ skills in architectural design, drawing, reading, creating new ideas in the design process.